Kewenangan Pemerintah Daerah Kabupaten Indragiri Hilir Dalam Penerbitan Perizinan Berusaha Pasca Lahirnya Undang-Undang Cipta Kerja - Wandi, Wandi; Ardiansyah, Ardiansyah; Riauan, Muhd Ar. Imam (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
Business licensing is a state administrative legal instrument used by the government to control business activities while ensuring legal certainty for business actors and the public. Since the enactment of Law Number 11 of 2020 concerning Job Creation, which was later re-established through Law Number 6 of 2023, the licensing system in Indonesia has undergone fundamental changes through the implementation of a risk-based business licensing approach and the digitalization of licensing through the Online Single Submission (OSS). These changes have also influenced the configuration of regional government authority, including the Indragiri Hilir Regency Government, in issuing business permits. This study aims to analyze the authority of the Indragiri Hilir Regency Government in issuing business permits after the enactment of the Job Creation Law, as well as to identify forms of coordination and obstacles to the implementation of this authority. The research method used is normative juridical with a statutory and conceptual approach. The research results show that the authority of the Regional Government has shifted from a conventional licensing model to an integrated licensing service model through the OSS, so that the Regional Government plays a greater role as a facilitator, service implementer, and supervisor of the fulfillment of licensing commitments according to norms, standards, procedures, and criteria (NSPK). However, in practice, obstacles remain, including limited system infrastructure, staff understanding, harmonization of regional regulations, and coordination between the central and regional governments. Therefore, strengthening regional institutional capacity, harmonizing regional regulations, and strengthening the integration of public service systems are necessary to ensure effective business licensing and ensure legal certainty in the regions.